Experiences of Sexual Objectification, Minority Stress, and Disordered Eating Among Sexual Minority Women. (December 2015) - Watson, Laurel B.; Grotewiel, Morgan; Farrell, Michelle; Marshik, Jessica; Schneider, Melinda
Our study extended a modified version of objectification theory to a sample of sexual minority women in order to understand their experiences with body image and disordered eating concerns. Specifically, reported experiences of heterosexist discrimination and internalized heterosexism were integrated into the objectification theory framework. A total of 243 U.S. sexual minority women (primarily White and lesbian) participated in our online study. Results of a path analysis and tests of direct and indirect relations elucidated the important role of heterosexist experiences in sexual minority women's eating disordered behaviors. Moreover, internalized sociocultural standards of beauty and internalized heterosexism were important predictors of sexual minority women's body image concerns. Overall, our results supported the applicability of tenets of objectification theory to sexual minority women, with some important modifications. Our study demonstrates the importance of attending to stressors that uniquely affect sexual minority women, which arise from a sexist and heterosexist sociocultural context.